2013
DOI: 10.3390/ijms140816719
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Protease Nexin-1 Protects against Cerebral Ischemia

Abstract: The serine protease thrombin plays a role in signalling ischemic neuronal death in the brain. Paradoxically, endogenous neuroprotective mechanisms can be triggered by preconditioning with thrombin (thrombin preconditioning, TPC), leading to tolerance to cerebral ischemia. Here we studied the role of thrombin’s endogenous potent inhibitor, protease nexin-1 (PN-1), in ischemia and in tolerance to cerebral ischemia induced by TPC. Cerebral ischemia was modelled in vitro in organotypic hippocampal slice cultures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As a glia-derived nexin, SERPINE2 is involved in regulating astrocyte proliferation, neurite outgrowth, neuron migration and localization, contributing to the development of brain, and the regeneration and reconstruction of neurons (38)(39)(40)(41). Our studies of EST profile showed that SERPINE2 expression begins to climb at early as the fetus stage, reaches a peak at the neonate and plateaus after the juvenile stage (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As a glia-derived nexin, SERPINE2 is involved in regulating astrocyte proliferation, neurite outgrowth, neuron migration and localization, contributing to the development of brain, and the regeneration and reconstruction of neurons (38)(39)(40)(41). Our studies of EST profile showed that SERPINE2 expression begins to climb at early as the fetus stage, reaches a peak at the neonate and plateaus after the juvenile stage (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, SERPINE2 may contribute to the development of the brain by modulating the proliferation and differentiation of cerebellar granular neuron precursors via the major mitogen SHH, as well as via granule neuron migration and positioning (41). SERPINE2 may exert protective activity in the pathalogical progression of intracranial hemorrhage (42), cerebral ischemia (40), and Alzheimer's disease (43). Again, the role of SERPINE2 in tumor progression in the brain seems to be a paradox.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism by which thrombin causes injury may relate to FXa (perinuclear activated factor X), which catalyzes the conversion of prothrombin to thrombin in neural tissue after ischemia [112]. Protease nexin-1 and L-JNKI1 were able to prevent the neuronal injury caused by thrombin [113,114]. …”
Section: Applications To Strokementioning
confidence: 99%
“…Circulating serum proteases, notably thrombin, fibrinogen, plasmin, kallikreins, and activated protein C (APC), enter the central nervous system (CNS) via injured blood brain barrier (De Luca et al, ; Petersen, Ryu, & Akassoglou, ; Radulovic et al, ). The action of thrombin on PAR1 is limited by endogenous antagonists, including protease nexin‐1(PN‐1) (Choi, Suzuki, Kim, Wagner, & Cunningham, ; Mirante et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(CNS) via injured blood brain barrier (De Luca et al, 2017;Petersen, Ryu, & Akassoglou, 2018;Radulovic et al, 2015). The action of thrombin on PAR1 is limited by endogenous antagonists, including protease nexin-1(PN-1) (Choi, Suzuki, Kim, Wagner, & Cunningham, 1990;Mirante et al, 2013).…”
mentioning
confidence: 99%